Physiology, Genetics, and Cardiovascular Disease: Focus on African Americans - Gibbons, Gary H (J Clin Hypertens (Greenwich), 2007)
The disproportionate impact of cardiovascular disease in African Americans is well recognized. Not only do risk factors such as obesity occur at a higher rate in the African‐American community, but this population experiences a greater mortality from cardiovascular disease than their white counterparts. The cardiovascular system is regulated in part by two opposing mediators linking the risk factors of obesity, vascular dysfunction, and diabetes. One of these mediators—angiotensin II–increases blood pressure, impairs endothelial function, decreases peroxisome proliferator activated‐receptor γ, and is proinflammatory, growth stimulating, profibrotic, and proatherogenic. The other mediator, peroxisome proliferator activated‐receptor γ, lowers blood pressure, improves endothelial function, decreases angiotensin II type 1 receptor function, and is anti‐inflammatory, growth‐inhibiting, antifibrotic, and antiatherogenic. Genotypic variants have been discovered that affect the functioning of both of these important systems. Some of these variants—like some genotypic variants discovered in the adrenergic system—occur with different frequencies in African Americans than in Americans of European descent and may help to explain racial/ethnic differences in susceptibility to cardiovascular disease and aspects of the response to treatment. Recognition of these genotypic differences may permit the development of therapies tailored to individual patients.